2005
DOI: 10.1111/j.1741-6612.2005.00122.x
|View full text |Cite
|
Sign up to set email alerts
|

How resident committees function in low‐level residential aged care facilities

Abstract: Objective: To investigate factors affecting the functioning of resident committees in South Australian low-level residential aged care facilities (RACFs). Methods: Observation of two consecutive resident committee meetings in 18 low-level RACFs. Results: Most meetings were informal. Only one-third had an agenda, and although all had minutes, only half provided them to residents. Most meetings were scheduled monthly, but because of postponements, meetings were held on average every 7 weeks. Many meeting rooms d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 5 publications
0
7
1
Order By: Relevance
“…A large discrepancy was also found with deciding what new activities would occur, with only a few residents feeling that they had substantial input into these decisions, whereas nearly half ideally wanted to help decide on new activities. This result is inconsistent with the results of an earlier study by the authors involving the same RACFs in which both residents and staff indicated that this was one of the main topics raised by chairpersons and staff for residents to comment on at resident committee meetings [4]. However, it may be that while the topic was raised, residents felt that their suggestions were not listened to or that nothing resulted from them.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…A large discrepancy was also found with deciding what new activities would occur, with only a few residents feeling that they had substantial input into these decisions, whereas nearly half ideally wanted to help decide on new activities. This result is inconsistent with the results of an earlier study by the authors involving the same RACFs in which both residents and staff indicated that this was one of the main topics raised by chairpersons and staff for residents to comment on at resident committee meetings [4]. However, it may be that while the topic was raised, residents felt that their suggestions were not listened to or that nothing resulted from them.…”
Section: Discussioncontrasting
confidence: 86%
“…Of 18 South Australian low‐level RACFs that participated in a previous study [4], 15 were able to participate in this study. All facilities were located in the Adelaide metropolitan area.…”
Section: Methodsmentioning
confidence: 99%
“…Governance refers to the power one has to be able to determine aspects of life and the importance of personal involvement in communal decision‐making. Wilson and Kirby [22] report that up to 65% of communities of older people have active residential committees. Resident comments around inability to vote in national elections and interest in facility annual plans and budgets show that residents are keen to remain active at all levels of governance.…”
Section: Discussionmentioning
confidence: 99%
“…It is quite common for aged care and residential facilities to offer exercise and activity programs to help maintain resident well-being. In addition, many aged care and living facilities have attempted to promote environmental action through waste minimization and resource usage strategies, adapted environments to be more health promoting, and established resident committees to ensure a more participative experience for residents (Kendig, 2003;Wilson and Kirby, 2005). These initiatives indicate a willingness of aged living and care settings to invest in the health and wellness of their population and the environment.…”
Section: Aging Of Populationmentioning
confidence: 96%